Śatakatrayam - Bhartṛhari,Rāmakṛṣṇa Śarmā Kṛṣṇamūrti,Kosambi, Dāmodar Dharmanand,Rāmarṣi,Gaṇapatarāva Yādavarāva (Ānandāśrame, 1977)
Three classical poems, comprising one hundred verses each on ethics love and renciation; includes commentary
Poems
Keywords: Sanskrit; Sprichwort